2016
DOI: 10.1007/s11356-016-7867-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary polyaromatic hydrocarbons are associated with adult emphysema, chronic bronchitis, asthma, and infections: US NHANES, 2011–2012

Abstract: Links between environmental chemicals and human health have emerged over the last few decades, but the effects from polyaromatic hydrocarbons were less studied, compared to other commonly known environmental chemicals such as heavy metals, phthalates, arsenic, phenols, pesticides, etc. Therefore, the aim of the study was to examine the relationships of urinary polyaromatic hydrocarbons and adult respiratory health conditions using a large human sample in a national and population-based setting in recent years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Our study also found that FLU was positively associated with SII, and the mediating effect showed that SII mediated the association between FLU and COPD prevalence risk, but other types of PAHs exposure levels were not significantly associated with SII. As a result of its association with chronic bronchitis, FLU has been linked to various lung diseases (26), emphysema, asthma (27), lung infection, and COPD, which in line with our study's findings (28).…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that FLU was positively associated with SII, and the mediating effect showed that SII mediated the association between FLU and COPD prevalence risk, but other types of PAHs exposure levels were not significantly associated with SII. As a result of its association with chronic bronchitis, FLU has been linked to various lung diseases (26), emphysema, asthma (27), lung infection, and COPD, which in line with our study's findings (28).…”
Section: Discussionsupporting
confidence: 91%
“…The selected studies were either review or cross-sectional studies. Exposure to PAHs was associated with diminished lung function and various respiratory symptoms and diseases, such as COPD and chronic bronchitis [ 60 , 61 , 62 , 63 ]. Furthermore, occupational exposure became evident in the review by van der Molen et al, 2018 [ 7 ], according to which diverse exposures at work to vapors, dusts, gases, and fumes (VDGF) were associated with COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four case-control studies, only two 48 , 49 gave eligibility criteria for case and control, sources of data and method of case ascertainment, and control selection. All twelve cross-sectional studies 17 18 , 26 , 29 , 34 41 reported inclusion and exclusion criteria, source of data, and method of selection of participants. Seven studies 8 , 39 40 , 45 , 47 , 48 , 50 did not explain how to control for confounding factors.…”
Section: Resultsmentioning
confidence: 99%
“…The studies in this review have a number of strengths. A significant proportion of the studies (twenty-two studies) 17 19 , 21 , 22 , 27 , 29 , 30 , 34 37 , 39 , 41 , 42 47 , 49 , 52 were conducted using a relatively large number of study participants ranging from 222 to 15 447. This has the statistical relevance of controlling for the risk of reporting false negative findings (type II error).…”
Section: Discussionmentioning
confidence: 99%